The Influence of Service Quality, Price, Promotion and Ease of Access on Consumer Buying Interest at Agung Supermarket Limboto - Tamahiwu, Rizki; Lamuda, Ilyas; Karundeng, Deby R. (LPPPIPublishing, 2025)
This study aims to analyze the influence of service quality, price, promotion, and ease of access on consumer buying interest in Agung Supermarket Limboto. The background of this research is based on the importance of effective marketing strategies in increasing consumer buying interest in the midst of fierce retail competition. The method used is a quantitative approach with data collection techniques through questionnaires that are distributed to consumers of Agung Supermarket Limboto. The data obtained were analyzed using multiple linear regression analysis. The results of the study show that the variables of service quality, price, promotion and ease of access have a positive and significant effect on consumer buying interest, both partially and simultaneously. These findings indicate that improvements in all four aspects can drive increased consumer purchasing decisions.